In‐situ interfacial polymerization endows surface enrichment of COOH groups on anion exchange membranes for efficient Cl−/SO42− separation. Issue 21 (9th December 2021) - Afsar, Noor Ul; Li, Xingya; Zhu, Yanran; Ge, Zijuan; Zhou, Yue; Zhao, Zhang; Hussain, Arif; Ge, Liang; Fu, Rongqiang; Liu, Zhaoming; Xu, Tongwen
Abstract: In‐situ interfacial polymerization technique is developed to prepare monovalent anion‐permselective membranes (MAPMs). The introduction of multi‐hydroxyl (OH) and cationic groups in the base membrane provide suitable routes towards the monovalent anion transport. Only trimesoyl chloride is employed to generate a crosslinked polyester layer on membrane surface. The ISIP transforms the surface of anion exchange membranes into a dense and negatively charged layer to promote the ion permselectivity. The modified membranes show a high limiting current density and low membrane resistance of 4.7 Ω cm 2 . The resultant membranes exhibit a high Cl − flux of 6.3 × 10 −8  mol cm −2  s −1 and a high permselectivity of ~60 for Cl − /SO4 2− . The findings demonstrate the ISIP technique having great potentials for the fabrication of highly permselective MAPMs. Abstract :